Current Therapeutic Strategies for Stem Cell-Based Cartilage Regeneration. (25th March 2018) - Nam, Yoojun; Rim, Yeri Alice; Lee, Jennifer; Ju, Ji Hyeon
Abstract : The process of cartilage destruction in the diarthrodial joint is progressive and irreversible. This destruction is extremely difficult to manage and frustrates researchers, clinicians, and patients. Patients often take medication to control their pain. Surgery is usually performed when pain becomes uncontrollable or joint function completely fails. There is an unmet clinical need for a regenerative strategy to treat cartilage defect without surgery due to the lack of a suitable regenerative strategy. Clinicians and scientists have tried to address this using stem cells, which have a regenerative potential in various tissues. Cartilage may be an ideal target for stem cell treatment because it has a notoriously poor regenerative potential. In this review, we describe past, present, and future strategies to regenerate cartilage in patients. Specifically, this review compares a surgical regenerative technique (microfracture) and cell therapy, cell therapy with and without a scaffold, and therapy with nonaggregated and aggregated cells. We also review the chondrogenic potential of cells according to their origin, including autologous chondrocytes, mesenchymal stem cells, and induced pluripotent stem cells.